2006
DOI: 10.1158/0008-5472.can-06-0634
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Functional Polymorphism in theTransforming Growth Factor-β2Gene Promoter and Tumor Progression in Breast Cancer

Abstract: Transforming growth factor-B (TGF-B), a multifunctional growth factor, plays an important role in breast cancer. There is increasing evidence that enhanced expression of TGF-B promotes breast cancer progression contributing to metastasis and invasiveness of the tumor. We identified a functional polymorphism in the TGFB2 promoter, a 4-bp insertion at position À246 relative to the transcriptional start site (À246ins). Transient transfection experiments showed that the À246ins polymorphism significantly increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…MAPKs consist of growth factor-regulated extracellular signal-related kinases (ERKs), and the stress-activated MAPKs, c-jun NH2-terminal kinases (JNKs) and p38 MAPKs21. Genes encoding components of TGF-β signaling pathway, including ligands TGF-β1 and TGF-β2 as well as receptor TGFBRI, are functionally polymorphic in humans22. TGF-β can regulate such diverse processes as cell proliferation, differentiation, motility, adhesion, organization, and programmed cell death17.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs consist of growth factor-regulated extracellular signal-related kinases (ERKs), and the stress-activated MAPKs, c-jun NH2-terminal kinases (JNKs) and p38 MAPKs21. Genes encoding components of TGF-β signaling pathway, including ligands TGF-β1 and TGF-β2 as well as receptor TGFBRI, are functionally polymorphic in humans22. TGF-β can regulate such diverse processes as cell proliferation, differentiation, motility, adhesion, organization, and programmed cell death17.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TGFB can cause immunosuppression and angiogenesis through acting on the surrounding stromal cells, immune cells, endothelial, and smooth muscle cells, which makes the cancer more invasive [35]. Downregulation and the pro-oncogenic effect of TGFB2 have been reported in human cancer [36,37]. However, little is known whether TGFB2 is involved in RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Amani et al [13] reported, for the first time, that the TGF- β 1 haplotype “GTGCCGC” might be associated with BC in Iranian woman. Several somatic mutations that disrupt the TGF β 1-Smad signaling pathway have been reported in human breast tumors [26, 42, 43]. These mutations may affect the different aspects of BC, including its occurrence, prognosis, progression, and metastasis.…”
Section: Tgf-β1 Tβr and Smad Mutations And Inactivationmentioning
confidence: 99%